Tindak Pidana Ringan dan Pengaturannya dengan Pendekatan Restorative Justice - Muhammad Muzayin Habibullah; Ifadah Pratama Hapsari (LPPM Universitas Ekasakti Padang, 2024)
Humans have been interacting with other people in what is known as civilization since they were born. He first communicated with his parents, and as he grew older, he lived in a society where people interacted with each other. Humans become aware of the fact that certain individuals in a society follow laws that govern their lives. A set of principles and guidelines that govern interactions between humans and society. In general, law plays an important role in social life because it guarantees legal certainty, as well as being a guide to justice, order, peace and order.